PENGAJARAN GURU PENDIDIKAN DASAR DI ERA MILLENIAL DALAM MEMBENTUK MORAL SISWA - Ari Susandi (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2019)
Elementary education is the first step to build student moral in introducing and basic teaching are needed a figure of teacher that ca be able to build whole student identity in this era state situation is getting more sophistiaced, aduance and do changes by creating something new that have a strong function in IPTEK development. At the bracelet III public elementary school institutions new sources there are still many students who are less active and focused in following the learning given by the teacher as well as the lack of learning innovation, hereby researcher interested to conduct research at education institution that have run at 1,2,3 August 2019 by open and close interview to teachers class I to VI it will be tested and result will be analysed in descriptively and qualitatively to answer the main case and qualitative data to know the score or percentage of the education proses that done by teacher class I to VI at SDN Gelang III Sumberbaru have they applied the best five indicator learing they are in personal approachement, meaning full learning, giving the feed back, sregthen the learning and also learning evaluation and taking the data by documenting of learning and also learning evaluation of elementary school teacher in era in building the student moral on 29-30 August at SDN Gelang III Sumberbaru Jember school year 2019-2020.the best five indicator learning is personal approachment meaningful learning.